Neuropeptide Y is Up-regulated and Induces Antinociception in Cancer-induced Bone Pain. (1st August 2018) - Diaz-delCastillo, Marta; Christiansen, Søren H.; Appel, Camilla K.; Falk, Sarah; Woldbye, David P.D.; Heegaard, Anne-Marie
Highlights: Neuropeptide Y is up-regulated in the spinal cord of cancer-bearing rats. Intrathecal neuropeptide Y induces antinociception in cancer-induced bone pain. The antinociceptive effect of neuropeptide Y is mediated by both Y1 and Y2 receptors. Abstract: Pain remains a major concern in patients suffering from metastatic cancer to the bone and more knowledge of the condition, as well as novel treatment avenues, are called for. Neuropeptide Y (NPY) is a highly conserved peptide that appears to play a central role in nociceptive signaling in inflammatory and neuropathic pain. However, little is known about the peptide in cancer-induced bone pain. Here, we evaluate the role of spinal NPY in the MRMT-1 rat model of cancer-induced bone pain. Our studies revealed an up-regulation of NPY-immunoreactivity in the dorsal horn of cancer-bearing rats 17 days after inoculation, which could be a compensatory antinociceptive response. Consistent with this interpretation, intrathecal administration of NPY to rats with cancer-induced bone pain caused a reduction in nociceptive behaviors that lasted up to 150 min. This effect was diminished by both Y1 (BIBO3304) and Y2 (BIIE0246) receptor antagonists, indicating that both receptors participate in mediating the antinociceptive effect of NPY. Y1 and Y2 receptor binding in the spinal cord was unchanged in the cancer state as compared to sham-operated rats, consistent with the notion that increased NPY results in a net antinociceptive effect in the MRMT-1 model. In conclusion, the data indicate that NPY is involved in the spinal nociceptive signaling of cancer-induced bone pain and could be a new therapeutic target for patients with this condition.